Quantitative Assessment of the Influence of Camera and Parameter Choice for Outdoor Electroluminescence Investigations of Silicon Photovoltaic Panels - Doll, Bernd; Del Rivero, E. Calderón; Hepp, Johannes; Pickel, Tobias; Buerhop, Claudia; Knecht, R.; Camus, C.; Hauch, Jens; Parisi, J.; Brabec, Christoph (Zeitschrift für Naturforschung Section A - A Journal of Physical Sciences, 2019)
With the spread of photovoltaics (PV) and increasing diversity in PV panel technology, quantitative comparison of the modules is highly desirable for consistent on-site quality assessment. Electroluminescence imaging reveals many defects, such as macroscopic crystal or electrical contact defects, but quantitative comparison outside the laboratory without controlled environment is still difficult, especially for different detector technologies. Here, we show how this problem can be addressed by adding reference spots in the module area: One passive dark spot and an active bright spot composed of a high-power back-contacted silicon PV cell. Those reference spots are used to evaluate the module's electroluminescence signal under different environmental conditions and to establish comparable results. Additionally, the comparison of images acquired with different camera technology detectors, such as silicon and InGaAs, is realised for signal levels.
CRIS-Team Scopus Importer:2019-07-12
Keywords: Defect Detection; Electroluminescence; Outdoor; Photovoltaic; Quantitative Comparison